Melissus and the Problem of the Void: Apology and/or Misapprehension of the Parmenidean Monism? - Volpe, Enrico (Peitho. Examina Antiqua, 2017)
With respect to Parmenides’ thought Melissus was regarded as a dissident thinker already in antiquity. His polemical introduction of the concept of void and the relative idea of infinite Being seemed particularly controversial. The aim of the present paper is to examine the origins of the Melissian understanding of void in order to trace its philosophical genesis to the criticism of the Atomist Leucippus. According to the philosopher from Abdera, the Eleatic fundamental principles had to conform to the obviousness of bodies’ motion, which is why the Eleatic not-Being had to be understood as void. Melissus took issue with this view and criticized the idea of the void’s reality by means of a methodical argument. In the course of doing so, the philosopher from Samos distorted the original Parmenidean ontology, which is why his theories were often criticized severely as theoretically weak.